2013
DOI: 10.1016/j.ydbio.2012.11.029
|View full text |Cite
|
Sign up to set email alerts
|

The combinatorial guidance activities of draxin and Tsukushi are essential for forebrain commissure formation

Abstract: We have shown that draxin is a repulsive axon guidance molecule for a variety of neuron classes and that genetic deletion of draxin in mice results in the absence of all forebrain commissures. Moreover, we also identified a secreted molecule, Tsukushi (TSK), that belongs to the small leucine-rich proteoglycan family (SLRP) and inhibits signaling molecules, such as BMP and Wnt. TSK knockout mice show malformation of the corpus callosum (CC) and agenesis of the anterior commissure (AC), suggesting the importance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…Notably, targeted inactivation of the Tsk gene in mice causes malformation of the corpus callosum, similar to the SPOCK1 mutants [ 596 ] (see below) and agenesis of the anterior commissure [ 597 ]. This forebrain commissure formation is co-regulated by draxin, dorsal inhibitory axon guidance protein [ 598 ]. Finally, tsukushi has been shown to control the hair cycles by regulating the TGFβ1/Smad pathway [ 594 ].…”
Section: Small Leucine-rich Proteoglycans/slrpsmentioning
confidence: 99%
“…Notably, targeted inactivation of the Tsk gene in mice causes malformation of the corpus callosum, similar to the SPOCK1 mutants [ 596 ] (see below) and agenesis of the anterior commissure [ 597 ]. This forebrain commissure formation is co-regulated by draxin, dorsal inhibitory axon guidance protein [ 598 ]. Finally, tsukushi has been shown to control the hair cycles by regulating the TGFβ1/Smad pathway [ 594 ].…”
Section: Small Leucine-rich Proteoglycans/slrpsmentioning
confidence: 99%
“…The role of TSKU in regulating cell differentiation has been previously suggested in several cell types including neuronal cells [4042]. For example, Hossain et al .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Hossain et al . showed that TSKU overexpression inhibited anterior olfactory neural and cortical neurite outgrowth [40]. Niimori et al .…”
Section: Discussionmentioning
confidence: 99%
“…The diverse functions of TSK depend on its ability to bind and interact with various intermediate molecules of some major signaling pathways. TSK interactions with BMP, FGF, TGF-β, and Wnt signaling pathways have been previously reported [1,[4][5][6] and shown to affect the development of the central nervous networks [7,8], as well as wound healing [9]. TSK is reportedly expressed in the chick retina [3,10], the subventricular zone and hippocampus in the mouse brain [8], and dermal hair follicles in mice [9].…”
Section: Introductionmentioning
confidence: 90%